2021
DOI: 10.1111/ijfs.14985
|View full text |Cite
|
Sign up to set email alerts
|

Selected nutritional quality and physicochemical properties of silkworm pupae (frozen or powdered) from two species

Abstract: This research was performed to examine selected nutritional quality and physicochemical properties of silkworm pupae. Frozen or powdered pupae from two species of silkworm (Bombyx mori and Samia ricinii) were studied. Eri had the largest size with the highest lightness and peak viscosity. The PCA (principal component analysis) total variance could be explained by 74.68%, and silkworm pupaes could be put into 2 clusters. Cluster 1: all varieties of frozen silkworm pupae having a high moisture content; Cluster 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
3
11
1
5
Order By: Relevance
“…However, defatting of crickets (Ribeiro et al, 2019) and deodorisation of yellow mealworm oil (Tzompa-Sosa et al, 2021) demonstrated positive effects on liking of final products. Hirunyophat et al (2021) reported differences in selected nutritional quality and physicochemical properties between frozen and powdered silkworm pupae prepared from two species (Bombyx mori and Samia ricinii). They further suggested that each variety of silkworm pupae had different properties that might be suitable for developing different novel food products.…”
Section: Hedonic Evaluationsmentioning
confidence: 99%
“…However, defatting of crickets (Ribeiro et al, 2019) and deodorisation of yellow mealworm oil (Tzompa-Sosa et al, 2021) demonstrated positive effects on liking of final products. Hirunyophat et al (2021) reported differences in selected nutritional quality and physicochemical properties between frozen and powdered silkworm pupae prepared from two species (Bombyx mori and Samia ricinii). They further suggested that each variety of silkworm pupae had different properties that might be suitable for developing different novel food products.…”
Section: Hedonic Evaluationsmentioning
confidence: 99%
“…In Thailand, silkworms are classified as mulberry (Bombyx mori) and non-mulberry or eri silkworm (Samia ricini), each of which has different nutritional value. Two main nutrients in the pupae of silkworms are protein and oil, which vary in the range of 48-67 wt% and 17-30 wt% (dry basis), respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Berger et al, (2018) demonstrated that hedonic claims are more appealing than rational ones to potential insect consumers, and repeat insect consumption behaviours will likely stem from enjoyable products and eating experiences (House, 2016). Insects and their potential as a food source have led to ample newly developed foods (Ardoin & Prinyawiwatkul, 2020; Ardoin et al, 2020; Hirunyophat et al ., 2021). Effective development of such foods will rely on thorough evaluations of ‘real’ insect‐based products (as opposed to rough concepts or model systems) by target consumers.…”
Section: Introductionmentioning
confidence: 99%